Effect of Biochar on Water Infiltration Characteristics of Iimestone Soil in Southwest Karst Area - YU Hui; FANG Rongjie; YU Jiajun; XU Qinxue; AO Liman; FU Zhiyong; CHEN Hongsong (Shuitu Baochi Xuebao)
[Objective] In order to explore the effect of corn straw biochar on water infiltration characteristics of calcareous soil in southwest karst area. [Methods] Five biochar application gradients (0, 2%, 4%, 6%, and 8%), three gravel content soils (10%, 20%, 30%) and no gravel soil were set up to carry out one-dimensional water infiltration test. [Results] (1) With the increase of biochar application rate, except for 10% gravel content, the migration depth of the wetting front gradually decreased, and the inhibition effect of adding biochar on gravel soil was weaker than that on non-gravel soil. Taking 60 min as an example, compared with CK (without gravel), it was reduced by 10%～27%, and the three gravel conditions were reduced by 1%～17%, 1%～16%, and 1%～21%, respectively. When the application amount was 8%, the migration depth of each treatment was the smallest. (2) Biochar reduced the cumulative infiltration of lime soil. The cumulative infiltration amount without gravel was 9%～27% lower than that of CK, while that with gravel was 11%～21% lower than that of CK. Among them, the cumulative infiltration amount was the least when the amount of gravel and biochar was 30% and 8%, respectively, and the amount of 2% had no significant effect. (3) With the increase of biochar application rate, the initial infiltration rate and stable infiltration rate of gravel-free soil decreased gradually. The effect of biochar on the stable infiltration rate of gravel soil is more significant than the initial infiltration rate. (4) Compared with the Philip model, both the Horton and Kostiakov models can be used to fit the soil water infiltration process in this study, but the fitting trend of the Horton model is more consistent with the actual results. [Conclusion] Corn straw biochar presents a promising solution for mitigating soil water infiltration in calcareous soil within karst regions. The distinguishing factor lies in the observation that the efficacy of corn straw biochar in mitigating soil water infiltration is less pronounced under gravel-infused conditions compared to homogeneous soil devoid of gravel. These findings offer valuable insights for the regulation of rainfall infiltration and effective soil moisture management in limestone-rich soils across the southwest karst landscape.